Do not Punish, Show Mercy: Clemency for the Condemned in Soviet Lithuania in 1954–1990 - Indrišionis, Darius (Genocidas ir rezistencija, 2019)
The article is concerned with the process of granting mercy to prisoners on death row in Soviet Lithuania. The Group for Granting Mercy consisting of members of the Presidium of the Supreme Council of the LSSR and other Soviet institutions (the Supreme Court of the LSSR, Public Prosecutor’s Department etc.) had the right to grant (or not to grant) mercy to convicts. From 1954 the group deliberated on a permanent basis requests for mercy of condemned criminals; from 1957 it deliberated clemency requests of political prisoners sentenced to death. Every individual facing the death penalty had the right to request for clemency. Besides, such requests were often submitted by his/her family, lawyers or other persons interested in the case. The strategy of clemency requests is different for different categories of the condemned: criminals sentenced to death were inclined to appeal to feelings, wrote about their young age, no criminal past, and being under the influence; economic criminals employed legal motifs and collaboration with the investigators; condemned to death political prisoners used a certain period of time (most often the time when they were in hiding) when their attitude to the Soviet regime was not hostile and it could serve as an evidence that they could be pardoned, could improve their behaviour and become “Soviet people”. Mostly clemency requests of condemned to death criminals (31.2 % of women) were granted; requests of economic (15.4 %) or political (7.1%) prisoners with capital sentences were fewer. Over the period under discussion, the Group for Granting Mercy of the Presidium of the Supreme Council of the LSSR deliberated a total of 301 requests for mercy submitted by the condemned to death, out of whom 77 individuals were pardoned. Seven more persons were absolved by the Presidium of the supreme Council of the USSR, which had more powers. Consequently, a total of 84 persons sentenced to death had their sentence commuted in the LSSS (27.9 % of all persons under death sentence).